The Relationship of Peer Social Support and Gratitude Towards the Meaningfulness of Life of People with HIV / AIDS (PLWHA) - Utama, Wirya Dipo (Basic and Applied Nursing Research Journal, 2023)
Introduction: of life is one of the critical variables in the lives of PLWHA. Social support and gratitude are among the factors that influence the meaning of life. This study aims to determine the relationship between peer social support and gratitude with the meaning of life in PLWHA. Methods: The respondents of this study were 44 people. Data were collected using a questionnaire that had been validated and tested for reliability. Results: The results of hypothesis testing showed a positive relationship between social support (rxy = 0.409; p = 0.007; p < 0.05) and gratitude with meaning of life (rxy = 0.338; p = 0.029; p < 0.05) in PLWHA. Conslusion: This indicates that the higher the social support and gratitude, the better the meaning of life of PLWHA.